2020
DOI: 10.3390/agriculture10030071
|View full text |Cite
|
Sign up to set email alerts
|

Application of Elemental Analysis via Energy Dispersive X-ray Fluorescence (ED-XRF) for the Authentication of Maltese Extra Virgin Olive Oil

Abstract: Elemental analysis using energy-dispersive X-ray fluorescence on extra virgin olive oils and seed oils revealed the presence of two major concentration related clusters, one containing elements of pedological origin, whilst the other consisted of heavy metals. Seed oils were found to contain a higher concentration of titanium when compared to extra virgin olive oils, whilst extra virgin olive oils derived from the Maltese Islands had a significantly higher concentration of barium and phosphorus on using the Kr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 23 publications
(32 reference statements)
0
8
0
Order By: Relevance
“…Whilst the 'Bidni' and 'Bajda' are monocultivars, the 'Malti' is thought to be made up of several ancient varieties which are geographically isolated from each other [22]. Furthermore, recent studies have shown that Maltese EVOOs have a significantly different phenolic composition and mineral composition [23,24]. In this study, a variety of olive oils selected from different areas around the Maltese islands and countries around the Mediterranean were studied.…”
Section: Introductionmentioning
confidence: 99%
“…Whilst the 'Bidni' and 'Bajda' are monocultivars, the 'Malti' is thought to be made up of several ancient varieties which are geographically isolated from each other [22]. Furthermore, recent studies have shown that Maltese EVOOs have a significantly different phenolic composition and mineral composition [23,24]. In this study, a variety of olive oils selected from different areas around the Maltese islands and countries around the Mediterranean were studied.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, many papers described ED-XRF as an accurate and rapid technique. ED-XRF has been already widely used for the verification of the geographical origin of olive oils [ 22 ] and different kinds of honey [ 23 ], the authentication and identification of drugs impurities [ 24 , 25 ], the elemental analysis of food products [ 12 , 26 ]. An analysis of the literature allowed us to find several drawbacks in previously conducted studies.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the quantitative analysis was conducted based on the theoretically calculated fluorescent X-ray intensities. The obtained results may be treated as semi-quantitative [ 22 ] and can be used to compare pollen of different origins or collected in different seasons. In addition, the great advantage of the qual–quantitative method is the identification of the unknown elemental composition.…”
Section: Discussionmentioning
confidence: 99%
“…Qualitative EDXRF analysis shows the spectral coverage of most elements present in the sample (atomic mass>13 in air atmosphere) at concentrations at the level of parts per million (ppm) by weight [24,25] . The EDXRF approach is not sensitive to lower‐Z elements in contrast to particle‐induced X‐ray emission (PIXE), which has a higher signal‐to‐noise ratio and fewer bremsstrahlung interactions, Rayleigh, and Compton scattering [26,27] .…”
Section: X‐ray Techniques For Materials Characterizationmentioning
confidence: 99%